EN FACE IMAGING OF PACHYCHOROID SPECTRUM DISORDERS WITH SWEPT-SOURCE OPTICAL COHERENCE TOMOGRAPHY. Issue 3 (March 2016) - Dansingani, Kunal K.; Balaratnasingam, Chandrakumar; Naysan, Jonathan; Freund, K. Bailey
Abstract : Purpose: To correlate clinical manifestations with choroidal morphology in pachychoroid disorders, including central serous chorioretinopathy, pachychoroid pigment epitheliopathy, pachychoroid neovasculopathy, and polypoidal choroidal vasculopathy, using en face swept-source optical coherence tomography (OCT). Methods: Patients with pachychoroid spectrum diagnoses were identified nonconsecutively through a review of charts and multimodal imaging. Each eye was categorized as uncomplicated pachychoroid, pachychoroid pigment epitheliopathy, central serous chorioretinopathy, pachychoroid neovasculopathy, or polypoidal choroidal vasculopathy. All patients included in this series then underwent bilateral swept-source OCT. Results: Sixty-six eyes of 33 patients were included. Numbers assigned to diagnostic categories were 8 uncomplicated pachychoroid, 13 pachychoroid pigment epitheliopathy, 27 central serous chorioretinopathy, 15 pachychoroid neovasculopathy, and 3 polypoidal choroidal vasculopathy. One eye was classified as normal. Swept-source OCT choroidal thickness maps confirmed increased thickness under the areas of pachychoroid pigment epitheliopathy, central serous chorioretinopathy, type 1 NV (pachychoroid neovasculopathy), or polyps (polypoidal choroidal vasculopathy). En face swept-source OCT showed dilated outer choroidal vessels in all eyes. In several eyes with a chronic disease, focal choriocapillaris atrophy with inward displacement of deep choroidal vessels was noted. Conclusion: Although clinical manifestations of pachychoroid spectrum disorders vary considerably, these entities share morphologic findings in the choroid, including increased thickness and dilated outer choroidal vessels. En face swept-source OCT localizes these changes to disease foci and shows additional findings that may unify our understanding of disease pathogenesis. Abstract : En face swept-source optical coherence tomography imaging of pachychoroid disorders, including pachychoroid pigment epitheliopathy, central serous chorioretinopathy, and pachychoroid neovasculopathy with or without polypoidal lesions, demonstrates a number of common choroidal findings that unify them into a spectrum. A number of novel features are described.